Pemberdayaan Masyarakat Melalui Program Kampung Tematik (Studi Kasus Kampung Tahu Tempe Gumregah di Kelurahan Lamper Tengah, Kota Semarang) - Anissa Kinanti; Priyatno Harsasto (Journal of Politic and Government Studies, 2019)
Poverty is one of the problems of government anywhere. The Semarang City Government to do acceleration prevention of poverty through a thematic village program. The purpose of thematic village program to optimize potency of the local environment by empowering local residents. The society must have high social capital to implement of empowerment. The purpose of researching to explain the implementation of society empowerment through thematic villages and the involvement of social capital. The method is used by qualitative. The interviewee is Bappeda of Semarang City, Lamper Tengah urban village, and society leaders. The location of researching was in the Tahu Tempe Gumregah village, the Lamper Tengah urban village, south of Semarang City sub-district. Technique of data collection uses interviews, observation, and documentation.The results of researching showed that the implementation of the thematic village program in the lamper tengah urban village did not run optimally.Bappeda is as government program representative or executor just only as drafter or planner and conduct monitoring and evaluation. Meanwhile, the implementation of the program is the area in the field or the area showed by government of Semarang city. There are some indicators in successful of empowerment. The existing social capital in the village of Tahu Tempe Grumegah is bonding social capital, which concerns the internal relations of the Tofu Tempe community. The Tempe tofu craftsmen group cannot establish relationships with other groups and is unable to take advantage of the authority of the Semarang City government.Conclusion of the researching: the government of Semarang City is in combating of proverty through thematic village programs has not been maximized. There are supporting factors that have not been utilized maximally by the local society. The Government of Semarang City is asked more actively in the empowerment prevention of poverty program.